Optimizing Knowledge In Teams: The Role Of Knowledge Orientation, Task, And Fit - McIntyre, David P. (Journal of Knowledge Management Practice, 2011)
Various scholars in economics, strategy, and organization theory have suggested that the integration of specialist knowledge is a key rationale for the existence of the firm, and that competitive advantage can result from the efficient flow of unique, valuable knowledge within the firm. Focusing on organizational teams, this paper will examine how the fit between a team’s knowledge orientation (specialist or generalist) and task orientation (the manner in which tasks are processed and shared within the team) has a significant impact on the knowledge integration process, and thus on team and firm performance. Implications for future research in this domain are discussed, with a particular emphasis on top management teams and virtual teams.